Influence of somatic cell count on milk components - Montanhini, Maike Taís Maziero (2013)
Mastitis is an inflammation in the mammary gland characterized by the changes in the glandular tissue, causing functional disorders in the affected mammary quarter. In its turn, these disorders promote de decrease on the milk production and changes in its centesimal composition, physical-chemical, bacteriology, and sensorial properties. This study aimed to evaluate the influence of somatic cell count (SCC) on the milk components. Were evaluated the results of 156.465 samples analyzed by the laboratory of Paraná Association of Holstein Breeders, between July and September of 2012. Were determined the SCC and the levels of protein, fat, lactose, total solids, casein and nonfat dry extract (NDE). The fat had the highest coefficient of variation, followed by the levels of casein protein, total solids, NDE, and finally the component that had the lower variation was the lactose. Among the samples tested, 47.4% had at least one result in disagreement with the limits stipulated by local legislation. For SCC, 21.8% of samples tested were above the standard. The fat content was positively correlated with SCC. Moreover, the lactose content and NDE showed a negative correlation with the SCC. The total protein level was not affected by SCC, however, casein showed a positive correlation with the SCC. Mastitis impacts in the milk quality, because it promotes significant changes in its components, especially fat, lactose and casein.